Treatment of Tooth Wear Associated with Reduced Occlusal Vertical Dimension Using Direct Composite Restorations and a Removable Prosthesis. Issue 1 (March 2021) - Caga, Daniel; Lewis, Nicholas
Tooth wear is increasing in prevalence within the United Kingdom. Treatment of tooth surface loss can be daunting for both the clinician and patient. However, use of additive resin composite restorations is a minimally invasive treatment modality. This case illustrates the treatment of tooth surface loss in both the maxillary and mandibular arches with direct composites restorations using putty indices generated from a diagnostic wax-up recorded in centric relation. The tooth surface loss had resulted in reduced restorative space on the right hand side. The restorative treatment involved increasing the anterior vertical dimension, enabling the provision of a cobalt-chrome partial denture. This case shows the restoration of form, function and aesthetics using a reorganised occlusal approach.